Implementation of Flipped Classroom in Islamic Education Lessons: Students’ Perspective - Nur'aini Nur'aini (AL-ISHLAH: Jurnal Pendidikan, 2021)
The research aims to assess flipped classrooms in Islamic religious education lessons at SMA Al-Azhar Batam. This research tries to illustrate students’ perspectives on the use of flipped classrooms in their classes. The respondents were 98 students who took Islamic religious education lessons.  This research uses the descriptive qualitative method. The data was analyzed based on responses found in the reflection sheet. The research showed that flipped classrooms enable students to control their learning, creating confusion and culture shock. Eventually, the researchers concluded with some suggestions for educators to adopt the flipped classroom technology to create better learning environments for their students and reach better learning consequences.  The teacher needs to make more precise and stricter instructions on using online materials for in-class learning.